2016
DOI: 10.5539/ies.v9n9p42
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Group Play Therapy on the Insecure Attachment and Social Skills of Orphans in Ahvaz City

Abstract: <p class="apa">This study aimed to determine the effectiveness of the group play therapy on the insecure attachment and social skills of orphans in Ahvaz city. Statistical population included all orphans in Ahvaz city, of whom 30 students were selected whose scores in insecure attachment and in social skills were one standard deviation higher and one standard deviation lower than the mean, respectively and they were randomly divided into two treatment (15 persons) and control (15 persons) groups. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Ice-breaking is done to increase familiarity and cooperation for students, researchers conduct ice-breaking by showing videos and games. Nasution (2018), Maharani (2018), Sahfriana (2015), Murphy (2019), Yuliatiningsih (2016), Mousavi (2016), andHadi (2018) in the study of social skills concluded that social skills can be improved by using several ways, namely by using problem-based learning Articles on the use of ice breaking for guidance media by Bakhtiar, the result that the development of ice breaking must be acceptable, have usefulness, accuracy, feasibility, and supporting social skills. Ice-breaking can improve social skills in students who are isolated, difficult to get along with, can improve cooperation, a sense of responsibility, self-development, communication, and confidence (Bakhtiar,2015).…”
Section: Student Drawing Resultsmentioning
confidence: 99%
“…Ice-breaking is done to increase familiarity and cooperation for students, researchers conduct ice-breaking by showing videos and games. Nasution (2018), Maharani (2018), Sahfriana (2015), Murphy (2019), Yuliatiningsih (2016), Mousavi (2016), andHadi (2018) in the study of social skills concluded that social skills can be improved by using several ways, namely by using problem-based learning Articles on the use of ice breaking for guidance media by Bakhtiar, the result that the development of ice breaking must be acceptable, have usefulness, accuracy, feasibility, and supporting social skills. Ice-breaking can improve social skills in students who are isolated, difficult to get along with, can improve cooperation, a sense of responsibility, self-development, communication, and confidence (Bakhtiar,2015).…”
Section: Student Drawing Resultsmentioning
confidence: 99%
“…Play therapy is one of the most important methods used to train children's social skills. It can also build connectivity and help solve behavioral problems for orphans in orphanages [41]. One of the characteristics of orphans is feeling insecure about their abilities, which is the main cause of most withdrawals from the surrounding environment.…”
Section: Discussionmentioning
confidence: 99%